Sustainable Development Comparative Analysis on State Banks and Regional Development Banks: Study Case in Indonesia - Aditya Pratama (Clean and Sustainable Production, 2023)
Increasing human activity has caused a decreasing environmental quality. This condistion will lead to a higher global warming impact. To minimize these negative impacts and improve sustainable living quality, the Indonesian government has a strategic initiative in the form of sustainable financing distribution. Apart from relying on government banks that have the ability to create financial stability, Indonesian government also relies on regional government banks that are capable to create regional financial stability. Referring to the strategy from the Indonesian government, this study will analyze the relationship between state bank financing and regional government banks with the SRI-Kehati sustainable development index. Regression results show that state banks have a relatively higher proportion of sustainable financing for the industrial sector by 13% compared with regional government banks at 11%. However, state banks only contributed 3% for the non-industrial sector compared with the regional government banks which has 6% contribution. In addition, the impulse-response results show that state banks have relatively more negative responses with no significant compared with the regional government banks. In relation to these findings, there is no type of bank that have most influential in building sustainable financing. However, both have their respective virtues in implementing decent sustainable financing if the government not only relies on government regulations and policies. However, ensuring the availability of a sufficient amount of financing and access to bank financing is expected to elevate better sustainable financing.